Empowering Women through Social Media-based Financial-Literacy Education Program - Leviastuti, Anggita; Santika, Tiara Devi; Prasetyo, Ilham (RSF Conference Series: Business, Management and Social Sciences, 2022)
In 2019 Indonesia’s financial literacy index stood at 38.03%, an improvement over time, but still considerably low compared to global standard. This number becomes even more disheartening when gender is taken into account as women in Indonesia have a noticeably lower financial literacy rate than men. This is the problem that we try to solve by presenting an approach for structuring and disseminating financial knowledge with the aim of improving financial literacy in Indonesia. We utilised a framework for social media knowledge management to develop a financial education program while simultaneously approaching the problem in exploratory manner by conducting in-depth interviews to gain understanding on various aspects of financial literacy. Judgement sampling technique was used for practicality purposes via in-depth interviews with 13 women who live in Bandung as the main object of the study. Among the respondents of our study, 76% were deemed well-literate while the rest were considered still literate. While encouraging, examining the data further shows that our respondents' understanding towards financial management is a bit more complicated and nuanced owing to a wide range of behaviour that our respondents exhibit.